Boosting integration capacity of electric vehicles: A robust security constrained decision making. (December 2021) - Vahidinasab, Vahid; Nikkhah, Saman; Allahham, Adib; Giaouris, Damian
Highlights: DRSs are optimally sized in long-term subject to the voltage stability constraints. The uncertainties are modeled using an IGDT-based framework. The effect of different integration scenarios on voltage stability margin is investigated. The role of responsive loads in improving the robustness of system is evaluated. Abstract: Global electric vehicles (EVs) fleet is expanding at a rapid pace. Considering the uncertain driving pattern of EVs, they are dynamic consumers of electricity and their integration can give rise to operational problems and jeopardize the security of the power system. Under such circumstances, the implementation of demand-side response (DSR) programs is more likely to be an effective solution for reducing the risks of load curtailment or security problems. This study proposes a voltage stability constrained DSR-coordinated planning model for increasing the penetration level of EVs in a distribution system consisting of photovoltaics (PVs), wind turbines (WTs) and responsive loads. The uncertainties of PV/WT generation, the driving pattern of EVs, and load demand are modeled by an improved form of information gap decision theory (IGDT), hereafter called weighted IGDT (WIGDT). Due to the fact that the proposed model is nonlinear and non-convex, a linearization technique is adopted and the proposed model is formulated as a mixed-integer linear programming (MILP), solved using the general algebraic modeling system (GAMS) software. The standard 33-bus distribution test system and a real-world smart distribution network, based in the Isle of Wight in the UK, are used to evaluate the performance of the model.